Pengaruh Pemanfaatan Teknologi Informasi Terhadap Penghayatan Iman Katolik Bagi Generasi Muda Deiyai Di Papua Tengah - Martinus Doo (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2024)
This study aims to analyze the impact of the use of information technology on the appreciation of the Catholic faith among young people in Central Papua. The research method used a quantitative approach with a survey of 150 Catholic teenagers in Deiyai district, Central Papua. Data were analyzed using simple linear regression to see the relationship between the intensity of information technology use and the appreciation of the Catholic faith. The results showed that the wise use of information technology has a positive influence on the appreciation of faith, especially through access to digital spiritual content. However, there are also challenges in the form of using technology for things that do not support the life of faith. This study recommends strategies to improve digital literacy based on Catholic faith values to optimize the positive impact of technology.